Early Active Exercise Improves MDA, SOD, and GSH Levels without Memory or NO Changes in Wistar Rats - Muhammad Hafiz Zuhdi Fairof; Arimi Fitri Mat Ludin; Nur Diyana Anas; Ainaa Husna; Ahmad Muhaimin Che Hasan; Amirul Hafiz Ahmad Abdullah; Farah Wahida Ibrahim; Adriyan Pramono; Nor Fadilah Rajab (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Circadian rhythms regulate various physiological processes, including responses to exercise. However, the effects of exercise timing on cognitive function and oxidative stress remain unclear. One key factor in oxidative stress is nitric oxide (NO), an enzyme complex that produces reactive oxygen species (ROS) as part of normal cellular signaling. Excessive NO activity can disrupt redox balance and contribute to neuronal damage. An imbalance favoring oxidative stress can impair memory and learning, while a higher antioxidant capacity supports brain health and cognitive performance. This study was performed to investigate whether early active and late active aerobic exercise differentially impact cognitive function and oxidative stress biomarkers in Wistar rats.METHODS: Sixteen male Wistar rats were randomly assigned to four groups: early active control, late active control, early active exercise, and late active exercise. The exercise groups underwent treadmill running for seven weeks, five days per week. Cognitive performance was assessed using the novel object recognition (NOR) test, while oxidative stress biomarkers, including malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione (GSH) were analyzed from brain tissue samples (hippocampus) following already established methods. Meanwhile the NO were assessed using Enzyme-linked Immunosorbent Assay (ELISA).RESULTS: This study showed that exercise timing did not significantly affect non-spatial memory performance. However, early active exercise led to a significant increase in SOD and GSH levels compared to the control and late active exercise groups, suggesting enhanced antioxidant activity. Conversely, late active exercise did not significantly impact oxidative stress markers. No changes was found in the NO concentration in both exercise timing.CONCLUSION: These findings suggest that exercise performed during the early active phase may be more beneficial for oxidative stress regulation, potentially contributing to long-term cognitive resilience.KEYWORDS: circadian rhythm, exercise timing, cognitive function, oxidative stress